Comparison of the effectiveness of aromatic ginger warm water bath with salt warm water against leg oedema of pregnant women in the third trimester - Aninora, Novia Rita; Handayani, Welly; Citra M, Resi (Science Midwifery, 2023)
Leg edema is found in around 80% of pregnant women in the third trimester, occurring due to pressure on the uterus which inhibits venous return and gravitational pull causing greater fluid retention. The aim of the research was to determine the comparison of the effectiveness of warm water soaking in aromatic ginger and salt warm water on leg edema of pregnant women in the third trimester in the Padusunan Padang Pariaman Health Center work area in 2023. The research design used was quasi-experimental with a two group pretest-posttest design. The sample of pregnant women who experienced lower limb edema was 52 people. Data processing uses a dependent t-test (paired sample t-test). The results of this study obtained the average level of edema in pregnant women in the third trimester before the warm water soak in aromatic ginger (3.62) and after (1.65). The average level of edema in pregnant women in the third trimester before the warm water soak was carried out salt (3.31) and after (1.96), Effectiveness before being given aromatic ginger warm water with warm salt water against leg edema in pregnant women in the third trimester (3-4) and after (1-3), There is effectiveness before and after giving aromatic ginger warm water with salt warm water against leg edema in third trimester pregnant women in the Padusunan Padang Pariaman Community Health Center work area in 2023 (p-value < 0.05). It is estimated that every pregnant woman who experiences edema during convulsions below should apply warm water immersion therapy to reduce the edema.